Analysis of offensive efficiency and goal scoring in the Stanley Cup Finals 2023 and 2024 - Luimula, S. (Baltic Journal of Sport and Health Sciences, 2025)
Background: The purpose of this study was to investigate the types of situations in which goals are scored at the highest level of ice hockey. The study focused on the Stanley Cup Final games (n=12).